2020
DOI: 10.1158/1078-0432.ccr-19-0098
|View full text |Cite
|
Sign up to set email alerts
|

Transient Sox9 Expression Facilitates Resistance to Androgen-Targeted Therapy in Prostate Cancer

Abstract: Purpose: Patients with metastatic prostate cancer are increasingly presenting with treatment-resistant, androgen receptor-negative/ low (AR À/Low ) tumors, with or without neuroendocrine characteristics, in processes attributed to tumor cell plasticity. This plasticity has been modeled by Rb1/p53 knockdown/knockout and is accompanied by overexpression of the pluripotency factor, Sox2. Here, we explore the role of the developmental transcription factor Sox9 in the process of prostate cancer therapy response and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Nevertheless, our spheres express high levels of several pluripotency genes, including NANOG, ALDH1A1, SOX2, OCT4 and KLF4, among others. Several studies have validated the implication of these genes in the regulation of the PCa stem cell niche, which confirms that these spheres retain stemness characteristics [33][34][35][36][37] . Indeed, our data indicate that a pattern of different embryonic pluripotency genes is crucial for the identification of docetaxel-resistant prostate CSCs.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, our spheres express high levels of several pluripotency genes, including NANOG, ALDH1A1, SOX2, OCT4 and KLF4, among others. Several studies have validated the implication of these genes in the regulation of the PCa stem cell niche, which confirms that these spheres retain stemness characteristics [33][34][35][36][37] . Indeed, our data indicate that a pattern of different embryonic pluripotency genes is crucial for the identification of docetaxel-resistant prostate CSCs.…”
Section: Discussionmentioning
confidence: 69%
“…GSEA indicated that KRAS_SIGNALING_UP and inflammatory signatures dependent on NF-κB or JAK-STAT3 signaling were amongst the top 10 Hallmark signatures induced by LDN193189 or enzalutamide (Figure 6P and S6N). The top genes within these signatures upregulated by LDN193189 included proteins potentially involved in prostate cancer therapy resistance and metastasis, such as the Notch ligand JAG1 (Domingo-Domenech et al, 2012), the lineage transcription factor SOX9 (Nouri et al, 2020), the inhibitor of apoptosis protein BIRC3 (Silke and Vucic, 2014), and the cytokine CCL2 (Su et al, 2019). In addition, CCL20 has been implicated in chemotherapy resistance in breast cancer (Chen et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…SOX9 is a recently discovered SOX family member that is up‐regulated in stem‐like reprogrammed prostate cancer cells. Transient SOX9 expression facilitates the resistance to enzalutamide via NF‐κB dimer activation (Nouri et al, 2020). Additionally, RE1‐silencing transcription factor ( REST ), another epigenetic remodelling regulator, mainly binds to chromatin in the proximity of neuron‐specific genes.…”
Section: Mechanisms Of Enzaluide Resistance In Castration‐resistant Pmentioning
confidence: 99%